Hubungan Antara Koordinasi Mata Kaki Dengan Kelincahan Pada Pemain Bulu Tangkis - Laksana, Bondan Tri, Wahyuni.S.Fis.,SKM.,M.Kes (2016)
Badminton it self in a sense is a game that uses a racquet and shuttlecock. The game is played by two people for a single game or four people for doubles. To be able to play properly, it must know and master the basic techniques of playing in a way that benarDalam game of badminton, besides the player must master the techniques Basically, players must have a rate of reaction in response to the direction shuttlecock coming, and in this case required the agility of foot-eye coordination is good. This study aimed to determine the relationship between foot-eye coordination with the agility of the badminton player. This research was correlative to determine the relationship between foot-eye coordination with the agility of the badminton player. The sample in this study were 30 taken through purposive sampling method, measurement of foot-eye coordination in this study using Wall Soccer Volleyball Test agility while for measurements in this study using the Shuttle Run test. Pearson correlative test test on a foot-eye coordination and agility gain significant value of p <0.05, which means that there is a relationship between foot-eye coordination and agility on pebulu in Karanganyar PB (p = 0.000). As for the correlation coefficient r value of -735 obtain meaningful eye coordination and agility leg strength strong correlation. The better the person's foot eye coordination, the better the value of agility owned. There is a relationship between foot-eye coordination with the agility of the badminton player